Materialist ethics and life-value - Noonan, Jeff (McGill-Queen's studies in the history of ideas, 2012)
Current patterns of global economic activity are not only unsustainable, but unethical - this claim is central to Materialist Ethics and Life-Value. Grounding the definition of ethical value in the natural and social requirements of life-support and life-development shared by all human beings, Jeff Noonan provides a new way of understanding the universal conception of "the good life." Noonan argues that the true crisis affecting the world today is not sluggish rates of economic growth but the model of measuring economic and social health in terms of money-value. In response, he develops an alternative understanding of good societies where the breadth and depth of life-activity and enjoyment are dependent on dominant institutions. The more social institutions satisfy the necessary requirements of human life, the more they empower each person to develop and enjoy the capacities that make human life valuable and meaningful. A well-reasoned synthesis of traditional philosophical concerns and contemporary critiques of global capitalism, this book is a forward-looking treatise that defends political struggle and reconsiders what is most important for a happy life.